Hiv Self Testing In Antenatal Care Services: A Systematic Literature Review - Sulistyawati, Feni; Widarini, Ni Putu; Mashudi, Sugeng (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2026)
Background: HIV continues to pose a serious threat to world health. Gestational age is one of the indicators used to evaluate the success of HIV status because pregnant HIV-positive women are more likely to experience maternal and perinatal morbidity and mortality. In order to reach pregnant women and their partners for HIV testing, the World Health Organization is beginning to explore the use of the most recent HIV test, known as HIV self-testing (HIVST). Determining the utilization of HIVST in ANC services is the aim of this literature review. Method: This article was written using a literature study based on Google Scholar and Pubmed databases from 2016-2023. A total of 17 articles are reviewed in this paper. Result: The results showed that the use of HIVST in pregnant women and their partners in ANC services was an early prevention related to status and further treatment efforts. Conclusion: It is hoped that the government will focus more on HIVST counseling and secondary HIVST distribution strategies in ANC services. In addition, further development is needed in the form of research related to HIVST in ANC services so that the target of HIV testing for pregnant women and partners can be achieved.